Public Private Partnership in Annuity Projects Model Concession Agreement - Planning Commission (Planning Commission, 2014)
Recognising that adequate investment in the development of infrastructure is a pre-requisite for higher growth, the Government has taken several steps to create an enabling environment to promote investment in infrastructure, especially investment from the private sector. As a result, the investment in infrastructure as a proportion of GDP increased from about 5 per cent in Tenth Plan to about 7 per cent in the Eleventh Plan, with the share of private sector increasing from 22 per cent to 37 per cent during the corresponding period. The Twelfth Plan envisages a further increase in investment in infrastructure, both in absolute terms as well as in the proportion of such investment to GDP. However, for achieving the envisaged level of investment, the share of private sector in infrastructure investment will have to increase significantly to about 48 per cent during the Twelfth Plan.
Planning Commission Government of India
Planning Commission Government of India